1986
DOI: 10.1017/s0022112086000630
|View full text |Cite
|
Sign up to set email alerts
|

Waves caused by a moving disturbance in a shallow channel of finite width

Abstract: The flow created by an impulsively started pressure distribution travelling at a constant velocity in a shallow channel is investigated. The restricted Green-Naghdi theory of fluid sheets is used to perform the three-dimensional calculations. The results show remarkable similarity to model tests. In particular, these calculations predict the periodic generation of two-dimensional solitons in front of and travelling faster than the disturbance if the disturbance is large enough. Behind the disturbance a complic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
101
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(110 citation statements)
references
References 15 publications
7
101
0
Order By: Relevance
“…Systematic experiments reported by Huang et al (1982), Ertekin et al (1984) and Lee et al (1989) established the presence of upstream propagating solitary waves. As well as the numerical simulations of the fKdV equation, simulations of a generalized Boussinesq equations by and Lee et al (1989), and of a Green-Naghdi model by Ertekin et al (1986) also confirmed the generation of upstream propagating solitary waves by transcritical flow over an obstacle.…”
Section: Introductionmentioning
confidence: 56%
“…Systematic experiments reported by Huang et al (1982), Ertekin et al (1984) and Lee et al (1989) established the presence of upstream propagating solitary waves. As well as the numerical simulations of the fKdV equation, simulations of a generalized Boussinesq equations by and Lee et al (1989), and of a Green-Naghdi model by Ertekin et al (1986) also confirmed the generation of upstream propagating solitary waves by transcritical flow over an obstacle.…”
Section: Introductionmentioning
confidence: 56%
“…Hence, numerical filtering of the result is necessary. Shown by Ertekin et al [17] for similar problems as that studied here, a combination of the five-(second-order) and seven-point (third-order) linear filtering schemes, developed by Shapiro [63], would ensure stability, while not altering the shape of the incident wave or the results. This includes the use of a third-order filtering in the direction normal to the prevailing wave crests, the ξ direction, and a second-order filtering parallel to the wave crests, the η direction.…”
Section: Numerical Solutionmentioning
confidence: 88%
“…The Level I GN equations are given here in the same form first presented by Ertekin [11] and Ertekin et al [17]. In this form of the equations, the fluid is inviscid, and the flow is incompressible, but irrotationality is not required.…”
Section: The Green-naghdi Equationsmentioning
confidence: 99%
“…In the last two decades, various studies were carried out by Wu and Wu,11,12 Akylas, 13 Ertekin, Webster and Wehausen, 14 Mei, 15 Lee, Yates and Wu, 16 Ertekin, Qian and Wehausen, 17 Teng and Wu 18,19 and others to investigate the nonlinear phenomenon of periodic production of upstreamradiating solitary waves ͑also called run-away solitons͒ by disturbances steadily moving at critical speeds in rectangular channels. Results showed that, for a rectangular channel, whether the disturbances ͑such as submerged moving objects͒ are two-or three-dimensional, the run-away solitons generated by them are invariably two-dimensional with a uniform crest across the channel.…”
Section: ͑1͒mentioning
confidence: 99%